Gastrointestinal histoplasmosis in a patient after autologous stem cell transplant for multiple myeloma. Issue 6 (10th November 2016) - Mohan, Meera; Fogel, Bradley; Eluvathingal, Thomas; Schinke, Carolina; Kothari, Atul
Abstract: A 59‐year‐old patient with multiple myeloma on maintenance chemotherapy presented with fever, weight loss, and night sweats. An F‐18 fluorodeoxyglucose (FDG) positron emission tomography (PET) computed tomography (CT) showed intra‐abdominal lymphadenopathy with a mesenteric mass that led to further workup and diagnosis of histoplamosis. The patient was treated with amphotericin B and subsequently switched to itraconazole. This exemplifies the usefulness of FDG PET CT in diagnosis of infectious complications.